The Urgency of Higher Education Institutions in Islamic Boarding Schools: To Maintenance and Development Islamic Values - Radinal Mukhtar Harahap (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Islamic boarding school has been known as a centre of Islamic values and national values. The efforts to maintenance and developt both of values are beginning from middle education and continue until higher education in islamic boarding school. However, most Islamic boarding schools are now stopped at the middle level. On the basis of literature, this paper tries to answer how is urgency of the existence of higher education for teaching Islamic values. The result of this research fouded existency of higher education in Islamic boarding schools is very needed to all aspects which are : theological aspects, psychological aspects, historical aspects and social aspects. The aim form existence of Islamic hinger institution to increase capabality student's understand and be able to analyze and solve their problems in society